Accounting for the environment / Rob Gray and Jan Bebbington ; editorial advisor, Martin Houldin. - Gray, Rob, 1952- (SAGE, 2001)
This text is an introduction and explanation of environmental issues as they relate to accounts today. Environmental concerns are of real importance to accountants because of the range of business issues they impact upon.